A prospective clinical review of "multi model" approach for treating ear keloids - Narakula Ganesh; Shenoy R (Indian Journal of Plastic Surgery)
This is a prospective clinical study of 46 ear keloids in 31 patients (with a mean follow-up of 18 months) treated from January 2006 to December 2006 at The Queen Elizabeth Public Hospital, Barbados, West Indies by a single surgeon. The mean age is 21.9 years (range 3-66 years). Seven out of 46 lesions were recurrent lesions following previous surgery. All the lesions were excised surgically (extralesional). Ten out of 31 patients were given postoperative, Intralesional Triamcinolone starting from the 1 st post operative visit on three visits at monthly intervals. Fourteen patients were given postoperative superficial X-ray therapy of 12 Gy in three equal fractions on three consecutive days starting from the 3 rd postoperative day. Seven recurrent keloids of this study were given a combination of both superficial X-ray therapy and intralesional triamcinolone. All patients were followed at monthly intervals for three visits from the time of surgery and every three months until the end of the 1 st year and then every six months thereafter. Five of 46 postoperative surgical wounds showed evidence of recurrence during the 1 st year but could be suppressed with Intralesional triamcinolone. This study confirms that surgical excision of keloids supplemented with radiotherapy and/Intralesional triamcinolone is a reliable method with few complications. In addition, the study concludes that the key in preventing recurrence is regular clinical follow-up to encounter early recurring lesion (clinical evidence of raised scars or palpable nodules if deep seated) which is 100% susceptible to Intralesional triamcinolone for 2-3 times at monthly intervals.